Utopian bodies and the politics of transgression - Sargisson, Lucy, 1964- (Routledge, 2000)
"Green political thought, feminism, the utopian canon and deconstruction meet in Utopian Bodies and the Politics of Transgression where they combine to form a new utopianism. This is transgressive utopianism, which, rather than blueprinting an ideal polity, creates new conceptual spaces for the exploration of alternative ways of being." "Here, bodies of thought meet bodies of people, and Britain's ecological, intentional communities are the starting place for a consideration of the roles of the public and the private, property, and relations of self and other. Together, Lucy Sargisson argues, these bodies address some of the most challenging dilemmas of contemporary political thought and life." "Utopian Bodies and the Politics of Transgression will be of interest to students and scholars of green political thought, feminist and utopian studies, as well as to philosophers and political theorists. People interested in intentional communities will find this an accessible introduction to some of their more radical implications."--Jacket